Health service delivery for type 1 diabetes during the lockdown in Uganda following the coronavirus disease 2019 pandemic - Silver Bahendeka; Thereza Piloya; Jasper Onono; Ronald Wesonga; Gerald Mutungi; Wenceslaus Sseguya; Denis Mubangizi (PAGEPress Publications, 2021)
Lockdown measures to reduce the spread of coronavirus disease 2019 (COVID-19), may adversely impact on diabetes supplies and metabolic control, especially in type 1 diabetes in low-resource countries. To address this, we conceptualized a service delivery model that incorporated a digitized tool. The digitized tool (UT1D-HIMAS) maintained electronic health records, monitored clinic supplies, patient clinic visits and admissions, and sent automated SMS messages. Delivery of supplies was by motor vehicles, motorcycles, bicycles or patients/caregivers walking to clinics. Metabolic control was assessed by glycated haemoglobin (HbA1c). Monitoring of clinic supplies including emergency restocking, patient clinic visits and admissions, and sending automated SMS by UT1D-HIMAS were successfully achieved. A fall in clinic visits, reaching a nadir (67.9%) in May 2020 was observed. HbA1c (mean ± SD mmol/mol) significantly (p= 0.040) worsened from 79.1 ± 26.8 to 94.9 ± 39.2 and (p=0.002) from 67.1 ± 22.7 to 84.8 ± 39.4 in the rural and urban clinic respectively. The digitized health information system exhibited high practicability in tracking stocks, clinic visits and hospitalisation but failed to improve metabolic control.